Clinical relevance and discriminatory value of elevated liver aminotransferase levels for dengue severity. - Linda K Lee; Victor C Gan; Vernon J Lee; Adriana S Tan; Yee Sin Leo; David C Lye (Public Library of Science (PLoS), 2012)
BACKGROUND: Elevation of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) is prominent in acute dengue illness. The World Health Organization (WHO) 2009 dengue guidelines defined AST or ALT ≥ 1000 units/liter (U/L) as a criterion for severe dengue. We aimed to assess the clinical relevance and discriminatory value of AST or ALT for dengue hemorrhagic fever (DHF) and severe dengue. METHODOLOGY/PRINCIPAL FINDINGS: We retrospectively studied and classified polymerase chain reaction positive dengue patients from 2006 to 2008 treated at Tan Tock Seng Hospital, Singapore according to WHO 1997 and 2009 criteria for dengue severity. Of 690 dengue patients, 31% had DHF and 24% severe dengue. Elevated AST and ALT occurred in 86% and 46%, respectively. Seven had AST or ALT ≥ 1000 U/L. None had acute liver failure but one patient died. Median AST and ALT values were significantly higher with increasing dengue severity by both WHO 1997 and 2009 criteria. However, they were poorly discriminatory between non-severe and severe dengue (e.g., AST area under the receiver operating characteristic [ROC] curve=0.62; 95% confidence interval [CI]: 0.57-0.67) and between dengue fever (DF) and DHF (AST area under the ROC curve=0.56; 95% CI: 0.52-0.61). There was significant overlap in AST and ALT values among patients with dengue with or without warning signs and severe dengue, and between those with DF and DHF. CONCLUSIONS: Although aminotransferase levels increased in conjunction with dengue severity, AST or ALT values did not discriminate between DF and DHF or non-severe and severe dengue.